2016
DOI: 10.1016/j.drugalcdep.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Visual and verbal learning deficits in Veterans with alcohol and substance use disorders

Abstract: Background This study examined visual and verbal learning in the early phase of recovery for 48 Veterans with alcohol use (AUD) and substance use disorders (SUD, primarily cocaine and opiate abusers). Previous studies have demonstrated visual and verbal learning deficits in AUD, however little is known about the differences between AUD and SUD on these domains. Since the DSM-5 specifically identifies problems with learning in AUD and not in SUD, and problems with visual and verbal learning have been more preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In particular, establishing whether aging substance abusers have cognitive difficulties over and above those that accompany normal aging (Blow, 1999; Searby et al, 2015) is an important first step. To date, few studies have investigated cognitive function in aging illicit drug users (Bell et al, 2016; Dowling et al, 2008; Iudicello et al, 2014), despite the established relevance of cognitive problems to both aging and drug use (Salthouse et al, 2003; Spronk et al, 2013; Stockel et al, 2017). Cognitive difficulties predict poor outcomes in psychotherapy for substance use disorders (Aharonovich et al, 2003; Aharonovich et al, 2006; Aharonovich et al, 2008), further emphasizing the need to investigate this question in relation to aging drug users.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, establishing whether aging substance abusers have cognitive difficulties over and above those that accompany normal aging (Blow, 1999; Searby et al, 2015) is an important first step. To date, few studies have investigated cognitive function in aging illicit drug users (Bell et al, 2016; Dowling et al, 2008; Iudicello et al, 2014), despite the established relevance of cognitive problems to both aging and drug use (Salthouse et al, 2003; Spronk et al, 2013; Stockel et al, 2017). Cognitive difficulties predict poor outcomes in psychotherapy for substance use disorders (Aharonovich et al, 2003; Aharonovich et al, 2006; Aharonovich et al, 2008), further emphasizing the need to investigate this question in relation to aging drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-seeking individuals with an alcohol use disorder (AUD) exhibit a range of neurocognitive (e.g., (Bates et al, 2002; Bell et al, 2016; Durazzo et al, 2006; Fein et al, 1990; Oscar-Berman et al, 2014; Pennington et al, 2013; Sullivan et al, 2000) and inhibitory control (de Wit, 2009; Naim-Feil et al, 2014; Rupp et al, 2016) deficits. A recent review describes deficits related to working memory, visuospatial functions, inhibition, and executive-based functions such as mental flexibility, problem solving, divided attention (Bernardin et al, 2014), and cognitive control (Wilcox et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that verbal learning and memory, rather than selective attention and executive function, were impaired among BD patients with and without AUD [21]. Impairment of verbal learning and memory was also found in previous clinical studies of participants with comorbid BD and SUDs [22,26,63]. AUD patients without BD have also shown impaired verbal learning and memory [64].…”
Section: Comparison With Other Studiesmentioning
confidence: 75%
“…BD patients with AUD exhibit less recovery from cognitive deficits than only BD patients [63]. However, one recent research showed that BD patients with comorbid AUD had initial delay but subsequent recovery in executive domain [65].…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
See 1 more Smart Citation